Thrombus Weight as a Measure of Hypercoagulability Induced by Drugs - MacIomhair, Maura; Lavelle, S M (Thrombosis and Haemostasis, 1979)
Thrombus weight was used as a measure of the thrombus enhancing effect of drugs in 135 rats. The weight of thrombus formed in one hour, on a 20 × 0.5 mm platinum wire, inserted in the vena cava was taken as a measure of thrombosis. The change in thrombus weight which followed the injection of ellagic acid to activate the coagulation system, adenosine diphosphate to activate the platelets, and epsilon-aminocaproic acid to inhibit the fibrinolytic system, was measured. Pilot studies showed that the drug doses used brought about the appropriate changes in the factors named. The mean thrombus weight in 45 control animals was 1.93 mg. Ellagic acid increased it about five-fold, and epsilon- aminocaproic acid almost two-fold, while adenosine diphosphate reduced it by almost a half. Concurrent controls were used in each case. Clotting tests (whole blood clotting time, kaolin-activated whole blood clotting time, thrombin time, and partial thromboplastin time), performed at the end of the hour, showed no significant correlation with thrombus weight.